“Meu dinheiro tem cor!”: afroempreendedorismo brasileiro e identidade - Nascimento, Eliane Quintiliano (2020)
The historical, social and economic elements are presented to demonstrate what, supposedly, drives the entrepreneurship of the black population in Brazil, which represents a majority in the country. Of the total Brazilian entrepreneurs, 51% declared themselves black, according to IBGE. Of these black entrepreneurs, Afro#entrepreneurs stand out: female entrepreneurs and self-declared black entrepreneurs who make their own business a means of social activism against the effects of racism, regardless of the type of business. Afro-entrepreneurship, in this research, is called an economic activity based on a network of ethnic solidarity, with collective objectives of valuing blackness, the practice of black money and the fight against racism, led by Afro-entrepreneurs and self-declared black consumers. The research analyzes two organizations that promote Afro-entrepreneurship in Brazil: Pretahub and the Black Money Movement. The convergence of the elements of black identity, entrepreneurship, consumption and the anti-racist struggle were investigated through content analysis on websites and field diaries. The conclusions point out that Afro#Entrepreneurship is directly linked to the construction of the political identity of contemporary black social movements.